REPRESENTASI PERILAKU MASYARAKAT INDONESIA DALAM IKLAN GRAB X OVO VERSI ‘MODAL PERCAYA – ASLI TJAP INDONESIA’ DI INSTAGRAM - Fandi Razan Fadhila; Hedi Pudjo Santosa; Amida Yusriana (Interaksi Online, 2023)
As a service provider company, Grab always publishes advertisements containing about its products. In taking advantage of the momentum of Indonesian independence, Grab collaborated with OVO to produce an advertisement entitled 'Capital Beli-Asli Tjap Indonesia' which displays a portrait of the behavior of Indonesian people in solving everyday problems. In this advertisement, there is no visible persuasive message conveyed at all. So, this advertisement is unique and differentiates it from previous versions of advertisements. This research aims to find out and describe how the behavior of Indonesian people is represented in these advertisements. This research uses Representation theory and the concept of Advertising - the magic of meaning as a basis for explaining the findings. The method used in this research is Semiotic analysis with data analysis techniques using two orders of significance. The results of the research show that Grab represents the behavior of Indonesian society through figures who have a fighting spirit, such as fathers, buskers, and manual field workers, represented as people who are persistent and optimistic, represented through several symbols such as sharpened bamboo, kerokan marks, areca nut climbing activities. , billboards for political officials, and superhero costumes. Grab inserts a message in the representation displayed, Grab is here as a practical solution in meeting needs and solving daily problems. Grab also inserts myths about celebrating poverty.